MANIPULATING L2 LEARNERS' ONLINE DICTIONARY USE AND ITS EFFECT ON L2 WORD RETENTION - Elke Peters (Language Learning and Technology, 2007)
This study explored the effect of two enhancement techniques on L2 learners' look-up behaviour during a reading task and word retention afterwards amongst Flemish learners of German: a Vocabulary Test Announcement and Task-induced Word Relevance. Eighty-four participants were recruited for this study. They were randomly assigned to one of two groups: 1) not forewarned of an upcoming vocabulary test (incidental condition) or 2) forewarned of a vocabulary test (intentional condition). Task-induced Word Relevance was operationalized by a reading comprehension task. The relevance factor comprised two levels: plus-relevant and minus-relevant target words. Plus-relevant words needed to be looked up and used receptively in order to answer the comprehension questions. In other words, the reading comprehension task could not be accomplished without knowing the meaning of the plus-relevant words. The minus-relevant target words, on the other hand, were not linked to the reading comprehension questions. Our findings show a significant effect of Test Announcement and Word Relevance on whether a target word is looked up. In addition, Word Relevance also affects the frequency of clicks on target words. Word retention is only influenced by Task-induced Word Relevance. The effect of Word Relevance is durable.